(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
It is time to rekindle the alert to strengthen and deepen, through educational exercise, cultural resistance, which has made us strong and achieve successes that seem impossible to achieve, defending the country from the coup attempt promoted by the serfs and vassals of the conquerors, reactivating the economy, production and promoting technological innovation, fighting the pandemic. We are a small town but one that knows where it is going and how to fight.